Distribución potencial del jaguar Panthera onca (Carnivora: Felidae) en Guerrero, México: persistencia de zonas para su conservación - Angela P. Cuervo-Robayo; Octavio Monroy-Vilchis (Revista de Biología Tropical, 2012)
Studies about the permanence of natural protected areas are important, because they contribute to the promotion of the conservation target and to optimize economical and human resources of specific areas. Although there are no natural protected areas in Guerrero, it has suitable habitat for the jaguar, a common species used for planning and management of conservation areas. Since, there is actual evidence that environmental and anthropogenic variables may modify vertebrate species distribution with time, in this study we predicted the potential distribution of Panthera onca using MaxEnt for this Southeastern region. In addition, we made a projection considering the effect of a moderate climate change scenario, to evaluate the stability of the conservation area for a period of 24 years. Furthermore, we applied three threat scenarios for the actual prediction to define conservation priorities areas. In our results, we have found that 18 361Km2 (29%) of this state has a permanent suitable habitat for jaguar conservation in the Sierra Madre del Sur and Pacific coast, with a possible loss of 2 000km2 in 24 years. This habitat is characterized by a 56% of temperate forest (mainly conifers and hardwoods 34%), and 35% of tropical deciduous forest. With the projections, the Southeastern region resulted with the higher anthropogenic impacts, while at the same time, an area of 7 900km2 in the Central-Western state was determined as a priority for conservation. To assure jaguar conservation, we propose the inclusion of this new conservation area, which is located in the Sierra Madre del Sur, with which we may potentially preserve other 250 species of threatened vertebrates. This way, the suggested habitat conservation may represent a local effort in Guerrero and will strengthen the biological corridor network for P. onca protection in Latin America.